Perlindungan Hukum Kepada Konsumen Terhadap Produk Skincare Tanpa Izin Edar Yang Dijual Secara Online - Atha Raihan Azayaka; Eko Wahyudi (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
This research was conducted with the aim of knowing legal protection for consumers for skincare products without a marketing authorization that are sold online. This study uses normative juridical research methods, namely using data collection techniques through library research or using secondary data. Among them are official documents, books, research results, in the form of reports. In this study, it was concluded that consumers who have experienced losses as a result of skincare products without marketing authorization can take legal action through the courts or outside the courts. However, this legal protection is still underutilized by consumers in the event of a problem, so that the UUPK becomes less effective, because compensation is given within seven days after the transaction. If this provision is maintained, it will be difficult for consumers who experience losses to obtain protection. This is because the negative effects of using skincare can occur after seven days.